A crise econômica e o desempenho financeiro das cooperativas de crédito brasileiras - Fernanda Alves Cordeiro (2018)
The general objective of this paper is to analyze the occurrence of possible impacts on the performance determinants of Brazilian credit cooperatives between 2015 and 2016 caused by the effects of the economic recession started in 2015 in Brazil. The dynamic panel approach was based on the GMM - Systemic methodology, due to the problem of endogeneity, present in the variables, and to the recursive characteristic of the performance proxies. The sample comprised 795 singular credit cooperatives listed in the Central Bank of Brazil (BACEN) database for the period from 2010 to 2016, excluding those classified as capital loans. The data embraced in the study refer to 73% of the total credit cooperatives in the country in December 2016. The econometric models constructed in this work allow us to conclude that the economic recession initiated in Brazil in 2015 impacted the performance of Brazilian credit cooperatives. The way in which instability has influenced cooperative performance is linked to the size of these institutions, as smaller institutions have been more exposed to risk compared to larger ones, which aim to obtain resources at scale. The study pointed to as a way of easing the obstacles caused by recessive periods to adopt non-conventional activities, that is, not linked to typical services, such as the provision of credit. The limitations of this research were the proxies used to evaluate the cooperative performance, since these institutions have intrinsic characteristics, related to the absence of strictly financial character and its social purpose. The achievement of non-financial variables capable of reflecting the particularities of credit cooperatives involves a complex construction process. Finally, this paper corroborates the literature on cooperativism discussing aspects related to the performance of credit cooperatives in scenarios of economic instability aiming therefore to reduce the gap in the study of the performance of cooperative institutions in periods of recession